(untitled) (Journal of Physical Education (Maringá), 2018)
We evaluated the negative effect of sarcopenic obesity (SO) on muscle strength, physical function and quality of life in obese elderly women using the appendicular lean mass (aLM) adjusted for BMI, and aLM adjusted for height and fat mass residuals approach. Participated fifty-eight obese elderly women aged 60 to 70 years separated by two groups (OS) and non-sarcopenic (OS) in two different approaches. The prevalence of SO was also verified between methods and its effects on handgrip strength, lean body mass, chair-stand test, time-up-and-go test, six-minute-walk test, peak O2 consumption, heart rate recovery and quality of life. The SO group presented significantly lower lean body mass, lower handgrip strength, inferior scores in the functional tests, inferior aerobic fitness, an impaired heart rate recovery, and an inferior aspect of quality of life as compared with the NSO group. Furthermore, no elderly woman was classified with SO by the aLM adjusted for height and fat mass residuals method. The cutoff-point addressed by the aLM/BMI represents a tool in clinical geriatric practice to identify and prevent this obesity/muscle syndrome in elderly women.